OUTCOMES FOLLOWING ZONE 3 AND ZONE 1 AORTIC OCCLUSION FOR THE TREATMENT OF BLUNT PELVIC INJURIES. Issue 5 (22nd May 2023) - Cralley, Alexis L.; Moore, Ernest E.; Dubose, Joseph; Brenner, Megan L.; Schaid, Terry R.; DeBot, Margot; Cohen, Mitchell; Silliman, Christopher; Fox, Charles; Sauaia, Angela
ABSTRACT: Background: A 2021 report of the Aortic Occlusion for Resuscitation in Trauma and Acute Care Surgery multicenter registry described the outcomes of patients treated with Zone 3 resuscitative endovascular balloon occlusion of the aorta (REBOA zone 3). Our study builds upon that report, testing the hypothesis that REBOA zone 3 is associated with better outcomes than REBOA Zone 1 in the immediate treatment of severe, blunt pelvic injuries. Methods: We included adults who underwent aortic occlusion (AO) via REBOA zone 1 or REBOA Zone 3 in the emergency department for severe, blunt pelvic injuries [Abbreviated Injury Score ≥ 3 or pelvic packing/embolization/first 24 hours] in institutions with >10 REBOAs. Adjustment for confounders was accomplished with a Cox proportional hazards model for survival, generalized estimating equations for intensive care unit (ICU)-free days (IFD) and ventilation-free days (VFD) > 0 days, and mixed linear models for continuous outcomes (Glasgow Coma Scale [GCS], Glasgow Outcome Scale [GOS]), accounting for facility clustering. Results: Of 109 eligible patients, 66 (60.6%) underwent REBOA Zone 3 and 43 (39.4%) REBOA Zone 1. There were no differences in demographics, but compared with REBOA Zone 3, REBOA Zone 1 patients were more likely to be admitted to high volume centers and be more severely injured. These patients did not differ in systolic blood pressure (SBP), cardiopulmonary resuscitation in the prehospital/hospital settings, SBP at the start of AO, time to AO start, likelihood of achieving hemodynamic stability or requirement of a second AO. After controlling for confounders, compared with REBOA Zone 3, REBOA Zone 1 was associated with a significantly higher mortality (adjusted hazard ratio, 1.51; 95% confidence interval [CI], 1.04–2.19), but there were no differences in VFD > 0 (adjusted relative risk, 0.66; 95% CI, 0.33–1.31), IFD > 0 (adjusted relative risk, 0.78; 95% CI, 0.39–1.57), discharge GCS (adjusted difference, −1.16; 95% CI, −4.2 to 1.90) or discharge GOS (adjusted difference, −0.67; 95% CI −1.9 to 0.63). Conclusions: This study suggests that compared with REBOA Zone 1, REBOA Zone 3 provides superior survival and is not inferior regarding other adverse outcomes in patients with severe blunt pelvic injuries.